Comparing the Lifestyle of Veteran and Non-Veteran Families - Seyed Alireza Afshani; Seyed Mostajad Hosseini-motlagh; Hamide Shiri-Mohammadabad (Journal of Social Behavior and Community Health)
Background: Considering the role of lifestyle in promoting, maintaining, continuity health and the importance of paying attention to the veterans and their families who have suffered a lot in order to sacrifice for the homeland, the present study intends to compare the lifestyle among veterans and non-veterans in Mashhad city. Methods: This study was conducted using a survey method. The statistical population included the veteran and non-veteran families of Mashhad. A total of 360 questionnaires were filled out in this city. The research instruments were Lifestyle Questionnaire (LSQ) and All Aspects of Health Literacy Scale. The data were analyzed by SPSS v.24. Results: There is not a significant difference between the mean scores of lifestyle in the two groups of veteran and non-veteran in Mashhad (p > 0.05). The comparison of mean lifestyle scores also showed that there was no significant difference between the lifestyle scores of men and women in the non-veteran group and the mean scores of the single and married lifestyle in the veteran and non-veteran group (p > 0.05). There is a significant relationship between education level and health literacy of veteran and non-veteran families with their lifestyle, age, and employment status. They are also related to the lifestyle of their life because of the status they provide for the sacrifices. Conclusion: Comparison of the two groups in terms of lifestyle indicates that the veterans are in a less favorable position than non-veterans in terms of some aspects of lifestyle such as physical health, exercise and health, disease prevention and mental health.